Economic analysis of climate change impacts on food security in North Africa (Morocco, Algeria, Tunisia, Egypt, Mauritania) - (:unkn) unknown (My University, 2022)
In North Africa, food security is highly vulnerable to climatic hazards, as it depends on traditional, largely rain-fed agriculture, which plays an important economic role. It is then expected that climate change will have impacts on food production, food availability and access even more difficult.The present thesis examines the economic impacts of climate change on food security in five North African countries, namely Mauritania, Morocco, Algeria, Tunisia, and Egypt over the period 1970-2018. The determinants of food security are expressed as a function of rainfall, temperature, CO2 emissions, arable land area, population size, and GDP per capita growth. Using the Auto Regressive Distributive Lag (ARDL) panel, we examined the economic impacts of climate change on food security in the short and long term.The results show that food security in North Africa is negatively but not significantly affected by temperature and CO2 emissions. However, rainfall, an increase in arable land area, and growth in GDP per capita will be beneficial for food security in the long term. Though, the short-term national coefficients show that climate change has a significant but mixed effect on food security in the five countries. The results also revealed that improved GDP per capita leads to improved purchasing power, and should support food security and improve welfare, thereby reducing macroeconomic vulnerabilities associated with food price volatility.Therefore, it would be important for policymakers in North Africa to explore and implement effective adaptation policies and employ technological advancement policies to mitigate the risks associated with increased rainfall levels especially in the short term, but more importantly to fight poverty to consolidate the economic, political and social development of the region.
Keywords: African Research